The Criminal Acts of Qisas and Diyat from the Perspective of Islamic Law - Hasan Munthe; Zaid Alfauza Marpaung (AT-TAFAHUM: Journal of Law, 2019)
This study aims to analyze the concept of qisas and diyat crimes from an Islamic legal perspective and their relevance in the context of modern law. Qisas is a form of punishment that is proportionate to the perpetrator of a crime, especially regarding the loss of life and body parts, while diyat is compensation or restitution given to the victim or the victim's family as an alternative to implementing qisas. Both concepts have a strong legal basis in the Qur'an and Hadith, which shows that Islamic criminal law has systematically regulated the protection of the right to life. The research method used is normative legal research with a conceptual and legislative approach. The data used are secondary data obtained through literature studies, including primary, secondary, and tertiary legal materials. Data analysis was conducted qualitatively by interpreting and reviewing various relevant legal sources. The research results show that qisas and diyat not only function as sanctions, but also embody the values of justice, humanity, and balance. Qisas provides a deterrent effect and ensures justice for the victim, while diyat opens up space for a more peaceful resolution through forgiveness. In the context of modern law, the concept of diyat shares similarities with the restorative justice approach, which emphasizes restoring the relationship between the perpetrator and the victim. Therefore, the values embodied in qisas and diyat remain relevant for study and can serve as a reference in developing a more humane and just criminal law.